PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DI SMA MUHAMMADIYAH 2 PALEMBANG - Fiarika Dwi Utari; Ikbal Barlian; Deskoni Deskoni (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2018)
This study aims to look at the Influence of Cooperative Learning Teams GamesTournament on Student Learning Outcomes in Subjects Economics at SMA Muhammadiyah 2Palembang. The formulation of the problem, namely “is there an influence of cooperativelearning teams games tournament against student learning outcomes on economic subjects inSMA Muhammadiyah 2 Palembang